Conflicts of Interest in Health Technology Assessments - Herrera Añazco, Percy (2024)
Health Technology Assessment (HTA) is a multidisciplinary process that systematically evaluates the properties, effects, and impact of health care technology; however, conflicts of interest may influence the selection of technologies to be evaluated or directly influence the process and decision-making. These conflicts of interest can invalidate an HTA, so it is considered important to declare them as a fundamental part of this process. However, despite its importance, not all agencies that develop HTAs worldwide include a declaration of conflicts of interest, so there is a risk of inefficient allocation of resources by providing coverage to interventions that offer little or no benefit or that prevent or delay patients' access to useful health technologies.